Perioperative BRAF inhibitors in locally advanced stage III melanoma. Issue 7 (26th June 2017) - Zippel, Douglas; Markel, Gal; Shapira‐Frommer, Roni; Ben‐Betzalel, Guy; Goitein, David; Ben‐Ami, Eytan; Nissan, Aviram; Schachter, Jacob; Schneebaum, Schlomo
Abstract : Background and Objectives: Stage III malignant melanoma is a heterogeneous disease where those cases deemed marginally resectable or irresecatble are frequently incurable by surgery alone. Targeted therapy takes advantage of the high incidence of BRAF mutations in melanomas, most notably the V600E mutation. These agents have rarely been used in a neoadjuvant setting prior to surgery. Methods: Thirteen consecutive patients with confirmed BRAF V600E regionally advanced melanoma deemed marginally resectable or irrresectable, were treated with BRAF inhibiting agents, prior to undergoing surgery. The primary outcome measures were a successful resection and pathological response. Disease‐free survival was a secondary outcome measure. Results: Overall, 12/13 patients showed a marked clinical responsiveness to medical treatment, enabling a macroscopically successful resection in all cases. Four patients had a complete pathological response with no viable tumor evident in the resected specimens and eight patients showed evidence of minimally residual tumor with extensive tumoral necrosis and fibrosis. One patient progressed and died before surgery. At a median follow up of 20 months, 10 patients remain free of disease. Conclusions: Perioperative treatment with BRAF inhibiting agents in BRAFV600E mutated Stage III melanoma patients facilitates surgical resection and affords satisfactory disease free survival.